Pengujian Aktivitas Antibakteri Minyak Atsiri Jahe (Zingiber Officinale Roscoe) Terhadap Bakteri Staphylococcus Aureus dan Escherichia Coli - Ali, Sufriyana; Baharuddin, Maswati; Sappewali, Sappewali (Al-Kimia, 2013)
Testing the antibacterial activity of the Essential Oil of Ginger (Zingiber officinale Roscoe) against bacteria Staphylococcus aureus and Escherichia coli. Purpose of this study is to determine the bacterial growht and activity test active compounds in ginger essential oils that can be used as an antibacterial to inhibit the growth of bacteria. This research uses a method soxhletation with solvent n- hexane to obtain the essential oil of ginger, making the media NA, rejuvenation bacteria, the manufacture of bacterial inoculum and suspension test. Antibacterial activity test using paper disc diffusion method in the form and method of dilution and analysis using GC-MS instrument. Antibacterial activity test result using paper disc method with a concentration of 25%,  50%, 75% and 100% in S. aureus (12, 34; 19, 42; 17, 34; 21, 7) mm and E. coli (10, 56; 13, 76; 16, 5; 23, 6) mm, while the result of the minimum inhibitory concentration (MIC) using ginger essential oil dilution method in S. aureus not found and E. coli at a concentration of 100%. The results of the analysis of essential oil components by GC-MS showed the active compounds in the form of compounds containing hydroxyl groups such as nerol, β- eusdesmol, borneol and compounds containing phenolic groups like zingerone.